Acute Invasive Fungal Rhinosinusitis in Children With Hematologic Malignancies: Outcome of Surgical Treatment. (17th November 2015) - Yakirevitch, Arkadi; Barg, Assaf Arie; Bedrin, Lev; Primov-Fever, Adi; Wolf, Michael; Migirov, Lela
Abstract : The incidence of acute invasive fungal rhinosinusitis (AIFR) is rising due to more aggressive chemotherapy and longer survival of immunosuppressed patients. Early diagnosis and appropriate but nonmutilating surgical treatment are particularly problematic in the pediatric population. This study aimed to evaluate the outcome of surgery for pediatric AIFR. Medical records of children surgically treated for AIFR between 1998 and 2014 were reviewed. Diagnosis was based on both histopathological and microbiological confirmation. Surgery was performed with curative intent and repeated for any resectable extension. The children underwent endoscopy and magnetic resonance imaging every 2 and 6 months, respectively, during the first postoperative year. Thirteen patients (2–18 years old) met the EORTC/MSG criteria for proven invasive fungal sinusitis; fungal invasion was diagnosed by preoperative biopsy and confirmed in the surgical specimen. All patients underwent an average of two endoscopic procedures (range 1–3), and four of them also underwent an open surgery. The local control rate was at least 79%. There was no facial disfiguration during follow-up (average 41 months). Although AIFR is still associated with high mortality, aggressive medical and surgical treatment provides local control in most cases. Fair outcome should encourage a maximal joint effort of pediatric hemato-oncologists and otorhinolaryngologists in the management of AIFR.